My neighbor Seki = Tonari no Seki-kun / vol. 3 - Morishige, Takuma, 1978-; Hinton, Yoshito; Morimoto, Mari (2015)
After putting up with so many distractions from her classroom neighbor Seki, Rumi Yokoi quietly begins to assert her will on a number of Seki's games.
"Originally published in Japanese as Tonari no Seki-kun 1 by Media Factory. Tonari no Seki-kun first serialized in Gekkan Comic Flapper, Media Factory, 2010-"--Title page.
vols. 3-10. Translation: Mari Morimoto.
Reads right to left.
Keywords: Comic books, strips, etc